Alternatif Lembar Kerja Peserta Didik Materi Osmosis Berbasis ANCORB: (Alternative Student Worksheets on ANCORB-Based Osmosis Materials) - Wiwin Kurniasih; Sri Anggraeni; Bambang Supriatno (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
Exsperiment method is the right method for learning biology. Osmosis is one of the important biological concepts and can be used to understand other biological concepts and requires exsperimental activities to better understand students. The implementation of exsperimental activities is guided by Student Work Sheets (LKS). The better worksheet, the better achievement of the exsperimenal objectives. However, only 24% of LKS in the field are suitable. This study aims to analyze and reconstruct LKS osmosis exsperiment on grade XI which has been used in high school and equivalent. The method used is descriptive qualitative with a sample of 10 worksheets about osmosis in different curriculum taken using total sampling. The instrument used was the LKS analysis instrument (conceptual, practical and knowledge construction) to determine the suitability of LKS with the curriculum and rubrics based on Vee Diagrams (Novak and Gowin, 2006) to support the analysis of knowledge construction. The results of the analysis using the LKS analysis instrument found the most dominant problems including: (1) cognitive problems: 7 content LKS does not match with KD and 7 LKS competence does not match with KD; (2) practical problems; 10 The worksheet does not include a time allocation; and (3) knowledge construction problems: 6 LKS do not require students to do data analysis, 6 LKS do not construct student knowledge. While the results of the analysis using Diagram Vee found only 3-4 LKS who achieved an ideal score (score 3) on each component of Diagram Vee. The conclusion from the analysis can be seen that the worksheet already has a conceptual, practical and knowledge construction component and a Vee Diagram component, but there are still some problems and the scores obtained are not yet optimal. So there is a need for reconstruction, especially on the components mentioned earlier. Abstrak. Metode praktikum adalah metode yang tepat untuk pembelajaran biologi. Osmosis adalah salah satu konsep biologi yang penting dan dasar untuk dapat memahami konsep biologi yang lainnya dan membutuhkan kegiatan praktikum untuk lebih memahamkan peserta didik. Pelaksanaan kegiatan praktikum dipandu oleh Lembar Kerja Peserta Didik (LKPD). Semakin baik LKPD, maka akan semakin baik juga ketercapaian dari tujuan praktikum. Namun LKPD yang berada di lapangan hanya 24% saja yang sesuai. Penelitian ini bertujuan untuk melakukan analisis, uji coba, rekonstruksi, dan membuat (ANCORB) alternatif LKPD praktikum osmosis di kelas XI yang selama ini digunakan di sekolah menengah atas dan sederajat. Metode yang digunakan adalah deskriptif kualitatif dengan sampel 10 LKPD mengenai praktikum osmosis pada kurikulum yang berbeda yang diambil menggunakan cara total sampling. Instrumen yang digunakan adalah instrumen analisis LKPD (analisis konseptual, praktikal dan konstruksi pengetahuan) untuk mengetahui kesesuaian LKPD dengan kurikulum dan rubrik berdasarkan Diagram Vee (Novak & Gowin, 1984) untuk mendukung analisis konstruksi pengetahuan pada LKPD. Hasil uji coba menunjukkan masih terdapat prosedur dan hasil praktikum yang kurang sesuai. Sedangkan berdasarkan hasil analisis menggunakan instrumen masih ditemukan berbagai masalah baik itu pada aspek kognitif, aspek praktikal, dan aspek konstruksi pengetahuan. Kemudian hasil analisis dengan menggunakan Diagram Vee, beberapa LKPD belum mencapai skor ideal. Sehingga perlu adanya rekonstruksi terutama pada komponen-komponen yang bermasalah untuk menghasilkan alternatif LKPD praktikum osmosis yang lebih baik.